Implementasi Penganggaran Dana Bantuan Operasional Sekolah Pada SMK Strada Budi Luhur Bekasi - Ana Maria Marlina; Dwiyatmoko Puji Widodo; Yuni Siti Nuraeni (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The school operational assistance fund (BOS) program created by the Ministry of Education and Culture in the implementation, management and reporting of funds must be guided by technical instructions for the use of school operational assistance funds (BOS) issued by the ministry of education and culture. This research aims to find out how school operational assistance funds (BOS) are managed. This research uses a qualitative approach with interview data collection techniques, documentation and descriptive methods based on the realization of school operational assistance funds (BOS). The results of the analysis are: 1) the management of school operational assistance funds (BOS) begins with the preparation of the RKAS with the coordination of a morning briefing, 2) the implementation of school operational assistance funds (BOS) is in accordance with the 2023 technical instructions, 3) reporting of school operational assistance funds (BOS ) which are made at the end of each stage, namely in June and December, are reported to the BOS Team by bringing a photocopied hardcover report to the Service Boss Team of each region, 4) Factors that hinder the distribution of school operational assistance funds from the center to schools (budgets are made from January , but the disbursement/decrease is in February), 5) by adding/improving school facilities we can improve student and school achievement..